Leadership Style and Information Technology Adoption on Knowledge Sharing Intention: A Structural Equation Modelling (SEM) Partial Least Square Approach - Novitasari, Dewiana; Young, Felina Co; Cahyono, Bambang Tri (International Journal of Social and Management Studies, 2024)
The purpose of this study is to investigate the effect of information technology adoption on knowledge-sharing intention by involving the leadership style variable as a mediator. The sample of this research was taken from 102 lecturers of a private university in Indonesia using a simple random sampling technique and using Structural Equation Model Partial Least Square (SEM-PLS) with SmartPLS version 4.0 software as a statistical tool. The results of this study indicate that information technology adoption has a positive and significant effect on knowledge-sharing intention, either directly or through leadership style mediation. Therefore, leadership style can be a variable mediator that strengthens the influence of information technology adoption on knowledge-sharing intention.